A Novel Script-Rule-Based Character Segmentation Method for Devanagari Script in a Natural Scene Image - Prasad , Vijay; Das , Pranab; Singh , Y. Jayanta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Devanagari script is one of the most popular and commonly utilized scripts across India. In this script, every character signifies a consonant sound along with an integral vowel sound. During the last decade, huge research is conducted for text localization and detection of various languages such as Japanese, English, Chinese, and others in scene images. However, there is limited research studies were performed on character segmentation for Devanagari Script. The existing methods used in the Devanagari script have some limits such as low accuracy in line, word, and character segmentation, dependency on handcrafted features in certain settings, computational complexity, and segmentation errors, etc. This research proposes a novel script-rule-based character segmentation model for the Devanagari script in a natural scene image setting. This proposed method is based on Deep Belief Network (DBN), Capsule Neural Network (CapsNet), and Naïve Bayes. Additionally, to recognize the middle region of the segmented region of the image, a modified recurrent neural network (RNN) model has been utilized. The measured performance metrics such as accuracy, precision, recall, and F1-score on Vpd Datasets using AdaDelta optimizer are 98.62%, 98,12%, 97.43%, and 97.01%, respectively. It is found that the proposed script rule-based character segmentation method obtains very optimized results.